2016
DOI: 10.1111/jace.14199
|View full text |Cite
|
Sign up to set email alerts
|

High‐Hardness Diamond Composite Consolidated by Spark Plasma Sintering

Abstract: A high‐hardness diamond‐based composite was synthesized by spark plasma sintering (SPS) under 100 MPa, using SiC‐coated diamond powder prepared via chemical vapor deposition (CVD). SiC layers 20–40 nm were uniformly deposited on diamond powders by a rotary CVD technique. The SiC‐coated diamond powder was consolidated with SiO2 powder by SPS at the sintering temperature of 1873 K, resulting in the formation of fully compacted mosaic microstructure with the Vickers hardness of 36 GPa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…On the contrary, the metal organic precursors such as hexamethyldisilane (C 6 H 18 Si 2 : HMDS) and polycarbosilane ([SH 2 CH 2 ] n : PCS) offer the advantage of lower deposition temperatures than silane and chlorosilanes; moreover, these precursors are less toxic and pyrophoric. 31)33) Figure 4 depicts micrographs of SiO 2 powder particles coated with SiC using rotary CVD with HMDS as an SiC precursor at a deposition temperature of 993 K. 21) Each spherical SiO 2 glass particle with a mean diameter of 250 nm (SO-E1, Admatechs Ltd.) was thoroughly coated with thin SiC layers of thicknesses ranging from a few nanometers to several tens of nanometers, as shown in Fig. 4.…”
Section: Sic-coated Sio 2 Compositementioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the metal organic precursors such as hexamethyldisilane (C 6 H 18 Si 2 : HMDS) and polycarbosilane ([SH 2 CH 2 ] n : PCS) offer the advantage of lower deposition temperatures than silane and chlorosilanes; moreover, these precursors are less toxic and pyrophoric. 31)33) Figure 4 depicts micrographs of SiO 2 powder particles coated with SiC using rotary CVD with HMDS as an SiC precursor at a deposition temperature of 993 K. 21) Each spherical SiO 2 glass particle with a mean diameter of 250 nm (SO-E1, Admatechs Ltd.) was thoroughly coated with thin SiC layers of thicknesses ranging from a few nanometers to several tens of nanometers, as shown in Fig. 4.…”
Section: Sic-coated Sio 2 Compositementioning
confidence: 99%
“…This dense diamond-based composite at the diamond content of 59 mass % (53 vol%) exhibited the high Vickers hardness value of 36 GPa. 20) At the interface of diamond and SiO 2 , a scanning transmission electron microscope (STEM) image [ Fig. 8(a)] and elemental mapping by electron energy-loss spectroscopy (EELS) [ Fig.…”
Section: )46)mentioning
confidence: 99%
“…26 Modern sintering techniques, such as pulse plasma sintering (PPS), SPS, electric discharge compaction, field-assisted sintering, pulsed-electric current sintering, and high-frequency induction-heated sintering under vacuum, at high speed and a relatively low temperature, are used to prevent graphitization. [27][28][29][30] Some studies have reported on the fabrication of the WC-Co/diamond composites with volume percentages of 20%-30% diamond using the HP-High temperature (HT) method 31 or PPS 3 and SPS 24 method, in which, in some cases, diamonds were coated with W 26 and SiC 30 to prevent diamond-to-graphite transformation during the sintering process. However, there is a research gap focusing the investigation of the effect of small volume percentages of diamond on the microstructure and mechanical properties of WC-Co composites using the SPS method.…”
Section: Introductionmentioning
confidence: 99%
“…The surface coating of hard phases could be effective to prevent the direct contact of hard phases. We have coated diamond particle with silicon carbide (SiC) by rotary chemical vapor deposition (CVD) to prevent the direct contact of diamond particle [27]. SiC coating also serves as an intermediate layer forming a strong bonding between the diamond particles and binder phase.…”
Section: Introductionmentioning
confidence: 99%